Strategi Konten Marketing Innovation Day dalam Meningkatkan Engagement Pada Media Sosial Tiktok - Putri, Tiara Imani Dirachma; Melano, Fiqie Lavani; Wijaksono, Dimas Satrio; Arifputri, Aiza Nabila (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Innovation Day was founded in 2016 as a forum for Telkom employees to share knowledge. In the TikTok account @innovationday there is an engagement target that must be achieved every month. In September there was no significant increase in engagement. The factors behind the lack of engagement are the lack of intensity in uploading content and the absence of an editorial plan on TikTok @innovationday. Therefore, the author intends to increase engagement on TikTok Innovation Day social media. The data collection method for designing TikTok social media comes from the author's observations, analysis and existing data. The theories used to discuss strategies for increasing TikTok Innovation Day social media engagement are the theories of Mass Communication, Marketing Communication, Content Marketing, Engagement, Social Media, TikTok, Content and Content Production. Innovation Day achieved a significant increase in engagement rates on the TikTok platform of 14.5%. The content marketing strategy implemented on TikTok Innovation Day was able to create a strong attraction and stimulate a positive response from the audience.